Heterogeneous Catalysts for C–C Bond Formation Reactions - Biswas, Subir; Devi, Arpita; Bora, Tonmoy J.; Bania, Kusum K. (Synlett, 2025)
Carbon–carbon (C–C) bond formation reactions have contributed significantly to the construction of numerous important molecules that have contributed in various dimensions. Heterogeneous catalysts that are recyclable and can convert a chemical reaction with the same affinity as that of the homogeneous counterpart provide an economically viable path. This account, therefore, focuses on different types of C–C bond formation reactions triggered by transition metal catalysts supported mostly on zeolite-Y and a few metal oxide nanocatalysts. The account comprises our recent works devoted to various C–C bond formation reactions performed by such heterogeneous catalysts including photocatalysts.1 Introduction2 Biaryl Synthesis by C–Cl Bond Activation3 Synthesis of 3,3′-Bis(indolyl)methanes4 C2 Trimerization of Indoles5 Cross-Aldol Condensation Reaction6 Friedel–Crafts Benzylation of Naphthol and Phenol7 Oxidative C–C Coupling of Naphthols8 Conclusion
Keywords: C–Cl bond activation; C2 trimerized indole; cinnamaldehydes; benzylation; naphthols; oxidative coupling; zeolite-Y